Risk factors and mortality in invasive Rasamsonia spp. infection: Analysis of cases in the FungiScope® registry and from the literature. Issue 3 (10th December 2019) - Stemler, Jannik; Salmanton‐García, Jon; Seidel, Danila; Alexander, Barbara D.; Bertz, Hartmut; Hoenigl, Martin; Herbrecht, Raoul; Meintker, Lisa; Meißner, Arne; Mellinghoff, Sibylle C.; Sal, Ertan; Zarrouk, Marouan; et al.
Summary: Background: The new Rasamsonia spp. complex can develop invasive infection in immunosuppression or chronic pulmonary disease. It has potential to be misidentified as other genera due to morphological similarities. Nowadays, there is a gap of knowledge on this fungi. Objectives: To provide knowledge base of risk factors and therapeutic decisions in invasive Rasamsonia spp. complex infection. Patients/Methods: Cases of invasive infection due to Rasamsonia spp. (formerly Geosmithia / Penicillium spp.) from FungiScope ® registry and all reported cases from a literature were included. Results: We identified 23 invasive infections due to Rasamsonia spp., six (26.1%) in the FungiScope ® registry. Main risk factors were chronic granulomatous disease (n = 12, 52.2%), immunosuppressive treatment (n = 10, 43.5%), haematopoietic stem cell transplantation (n = 7, 30.4%), graft‐versus‐host disease and major surgery (n = 4, 17.4%, each). Predominantly affected organs were the lungs (n = 21, 91.3%), disease disseminated in seven cases (30.4%). Fungal misidentification occurred in 47.8% (n = 11), and sequencing was used in 69.6% of the patients (n = 16) to diagnose. Breakthrough infection occurred in 13 patients (56.5%). All patients received antifungal treatment, mostly posaconazole (n = 11), caspofungin (n = 10) or voriconazole (n = 9). Combination therapy was administered in 13 patients (56.5%). Susceptibility testing showed high minimum inhibitory concentrations for azoles and amphotericin B, but not for echinocandins. No preferable treatment influencing favourable outcome was identified. Overall mortality was 39% (n = 9). Conclusion: Rasamsonia spp. are emerging fungi causing life‐threatening infections, especially in immunocompromised and critically ill patients. Mortality is high. Treatment is challenging and clinicians dealing with this patient population should become aware of this infection constituting a medical emergency.